LANDBALL RULES AND GAME TACTICS - Sharipov Odilbek Abdiqaaxhorovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article shows that the basis of the game of handball is the formation of natural movements that help the participants to develop in all respects, such as running, jumping, passing the ball, throwing.